From Hardcoded Keys to Centralized Control: Modern Approaches to Secret Management - Piotr KONTOWICZ (Communications of International Proceedings, 2025)
The growing complexity of modern IT environments, supported by cloud computing, microservices, and DevSecOps practices, makes secret management an essential component of organizational security. Secrets, including API keys, credentials, and cryptographic keys, enable authentication between human and system entities. Their compromise leads to severe data breaches and operational disruption. Existing literature and standards, such as NIST and ISO 27001, provide guidance for key management, yet there remains a clear gap in integrating technical, procedural, and compliance perspectives into one consistent framework. This study addresses this gap through an analytical review of modern secret management mechanisms, focusing on software-based secret managers, key management services, and hardware security modules. The analysis examines how each solution contributes to confidentiality, integrity, and availability in distributed systems and evaluates security challenges related to cloud and hybrid environments. The findings show that effective secret management requires not only the implementation of technology but also the development of comprehensive policies, automation, and awareness programs. Centralization, lifecycle control, and adherence to the principle of least privilege are essential elements that strengthen protection against unauthorized access. Combining technology, processes, and education results in higher organizational resilience and positions secret management as a fundamental pillar of modern cybersecurity.
Keywords: Secret Management; Cryptographic Keys; DevSecOps; Cloud Security; CIA Triad; Key Management; Security Policy